2019
DOI: 10.1111/1471-0307.12613
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids, health indices and sensory properties of Ricotta cheese from sheep fed three different diets

Abstract: The study evaluates the healthy fatty acid profile and sensorial characteristics of Ricotta obtained from ewes fed three different diets: diet enriched with linseed (L), un‐supplemented diet (F) and pasture (P). Omega‐3 fatty acid (n‐3 FA) levels in Ricotta from grazing sheep and from animals that received the supplemented diet were notably higher than those that received un‐supplemented feed. The L‐ and P‐groups had lower levels of saturated fatty acids (SFAs), higher levels of conjugated linoleic acid (CLA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
3
14
0
Order By: Relevance
“…This substitution is advantageous due to its low fat and lactose levels, besides the improvements in the nutritional properties (Kelly, 2019a). However, it is an ingredient with a high cost of production, requiring great demand, production planning, and market strategies for compensation (Araque et al, 2018;Fusaro et al, 2019). Therefore, supermarket chains are still the main routes for the commercialization of whey-containing products.…”
Section: Resultsmentioning
confidence: 99%
“…This substitution is advantageous due to its low fat and lactose levels, besides the improvements in the nutritional properties (Kelly, 2019a). However, it is an ingredient with a high cost of production, requiring great demand, production planning, and market strategies for compensation (Araque et al, 2018;Fusaro et al, 2019). Therefore, supermarket chains are still the main routes for the commercialization of whey-containing products.…”
Section: Resultsmentioning
confidence: 99%
“…Fresh pasture has been shown to be an excellent source of polyunsaturated fatty acids (PUFA) to increase these FA in milk [5] and, subsequently, in suckling lamb meat fat [6]. Unfortunately, in Italy, like in other Mediterranean countries, fresh pasture is not available all year, and in this case, linseed supplementation (oil or seed) is a reliable alternative feeding strategy to enrich the milk fat from ewes [5,7,8] with PUFA, Conjugated Linoleic Acid (CLA), or omega three (n-3), and for their suckling lambs.…”
Section: Introductionmentioning
confidence: 99%
“…Derivatives made of sheep milk have been recently studied, including Ricotta cheese (Fusaro et al, 2019), ice cream with probiotic (Balthazar et al, 2018b), beverage with strawberry (Balthazar et al, 2018a) and milk-juice beverage with fermented milk (Balthazar et al, 2019). Studies with sheep milk and derivatives have demonstrated that they are good sources of proteins and minerals (Balthazar et al, 2019), beneficial fatty acids such as α-linoleic acid and conjugated linoleic acid (Renes et al, 2018;Fusaro et al, 2019), in addition to their unique sensorial characteristics and functional properties (Balthazar et al, 2018a(Balthazar et al, , b, 2019Fusaro et al, 2019).…”
Section: Introductionmentioning
confidence: 99%